2016
DOI: 10.1016/j.nbd.2016.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Altered cholesterol biosynthesis causes precocious neurogenesis in the developing mouse forebrain

Abstract: We previously reported a mutation in the cholesterol biosynthesis gene, hydroxysteroid (17-beta) dehydrogenase 7 (Hsd17b7rudolph), that results in striking embryonic forebrain dysgenesis. Here we describe abnormal patterns of neuroprogenitor proliferation in the mutant forebrain, namely, a decrease in mitotic cells within the ventricular zone (VZ) and an increase through the remainder of the cortex by E11.5. Further evidence suggests mutant cells undergo abnormal interkinetic nuclear migration (IKNM). Furtherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 55 publications
0
29
0
Order By: Relevance
“…Mechanistically, Spot14 decreases FASN activity by dimerizing with Mig12, an activator of ACC, thereby inhibiting its function and causing a decrease of ACCmediated malonyl-CoA production, leading in a reduction in FA synthesis (Knobloch et al, 2013). Of note, it was suggested that cholesterol biosynthesis, which occurs through an independent pathway, is also required for NSPC self-renewal and maintenance in the developing mouse forebrain, as NSPCs with mutations in enzymes involved in this pathway exhibit premature differentiation into neurons, causing exhaustion of the stem cell pool (Driver et al, 2016). Importantly, as in the case of NSPCs, increased lipid anabolism in Drosophila GSCs through the activation of SREBP also resulted in stem cell loss (Sênos Demarco et al, 2019), suggesting that a conserved mechanism may be at play across stem cell populations.…”
Section: De Novo Lipid Synthesis In Stem Cellsmentioning
confidence: 99%
“…Mechanistically, Spot14 decreases FASN activity by dimerizing with Mig12, an activator of ACC, thereby inhibiting its function and causing a decrease of ACCmediated malonyl-CoA production, leading in a reduction in FA synthesis (Knobloch et al, 2013). Of note, it was suggested that cholesterol biosynthesis, which occurs through an independent pathway, is also required for NSPC self-renewal and maintenance in the developing mouse forebrain, as NSPCs with mutations in enzymes involved in this pathway exhibit premature differentiation into neurons, causing exhaustion of the stem cell pool (Driver et al, 2016). Importantly, as in the case of NSPCs, increased lipid anabolism in Drosophila GSCs through the activation of SREBP also resulted in stem cell loss (Sênos Demarco et al, 2019), suggesting that a conserved mechanism may be at play across stem cell populations.…”
Section: De Novo Lipid Synthesis In Stem Cellsmentioning
confidence: 99%
“…Given the role of cholesterol in the RBC membrane, it is plausible that cholesterol regulates cell survival. However, the function of the CSP might not be limited to cell death or stress mechanisms because previously published work has indicated a regulatory function for cholesterol and its derivatives at the level of cellular differentiation [53][54][55][56][57][58][59][60] . Future work that analyzes both primitive and definitive hematopoiesis at unique stages of differentiation in different model systems is likely to identify the exact cellular mechanisms underlying the phenotypic alteration we describe.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, decreased Chol biosynthesis has little effect on NSPC proliferation when compared to its effect on newborn neurons, which undergo massive death by apoptosis when Chol is limited. Similarly, the radial glial network that supports the migration of newborn neurons also seems to be affected by changes in Chol [139,140]. Consequently, reduced Chol levels at cell membranes seems to compromise brain neurogenesis and NSPC migration.…”
Section: Protein-lipid Interactions In Neuroregenerationmentioning
confidence: 99%
“…Consequently, reduced Chol levels at cell membranes seems to compromise brain neurogenesis and NSPC migration. Weaker Chol biosynthesis affects the mitotic behavior of NSPCs and it induces premature differentiation into neurons, which could explain why newborn neurons undergo apoptosis in these conditions [140]. Interestingly, these defects can at least be partially prevented by feeding pregnant animals Chol supplemented diets [140].…”
Section: Protein-lipid Interactions In Neuroregenerationmentioning
confidence: 99%